Elucidating posttraumatic stress symptom profiles and their correlates among women experiencing bidirectional intimate partner violence. - Hellmuth, Julianne C; Jaquier, Véronique; Swan, Suzanne C; Sullivan, Tami P (Journal of clinical psychology, 2014)
This study employed latent class analysis to identify profiles of women experiencing intimate partner violence (IPV) based on the severity of posttraumatic stress disorder (PTSD) symptoms.
Keywords: Adult; Crime Victims; Depression; Female; Humans; Middle Aged; Severity of Illness Index; Spouse Abuse; Stress Disorders, Post-Traumatic